2003
DOI: 10.1086/375855
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeSpectroscopy of the Unexpected 2001 July Outburst of the Dwarf Nova WZ Sagittae

Abstract: We present Hubble Space Telescope (HST) Space Telescope Imaging Spectrograph E140M spectra of the dwarf nova WZ Sge, following the early superoutburst of 2001 July. Our four far-ultraviolet (FUV) spectra, obtained over a time span of 4 months, monitor changes in the hot component of the system during the decline phase. The spectra cover the wavelength interval 1150-1708 Å . They reveal Stark-broadened Ly and He ii (1640) absorption and absorption lines due to metals (Si, C, N, Al) from a range of ionization st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…In these systems, the WD was first recognized in IUE spectra from the broad Ly absorption and the fact that WD model fits to these spectra yielded temperatures and luminosities that were consistent with the estimated distances to these DNe (Panek & Holm 1984;Mateo & Szkody 1984;Holm 1988). The IUE results were then confirmed with higher signal-to-noise ratio (S/N) observations made with the Hopkins Ultraviolet Telescope (HUT), the Hubble Space Telescope (HST ), and the Far Ultraviolet Spectroscopic Explorer (FUSE; Long et al 1993Long et al , 1994aLong et al , 2003Sion et al 1994Sion et al , 1995Sion et al , 2003Froning et al 2001;Godon et al 2004). In these data, the WDs are recognizable not only from the broad Ly and Ly absorption lines and the overall shape and flux of the UV spectrum but also from the relatively narrow metal absorption lines, which result from the salting of the atmosphere of the WD by accreting near-solar abundance material.…”
Section: Introductionmentioning
confidence: 67%
“…In these systems, the WD was first recognized in IUE spectra from the broad Ly absorption and the fact that WD model fits to these spectra yielded temperatures and luminosities that were consistent with the estimated distances to these DNe (Panek & Holm 1984;Mateo & Szkody 1984;Holm 1988). The IUE results were then confirmed with higher signal-to-noise ratio (S/N) observations made with the Hopkins Ultraviolet Telescope (HUT), the Hubble Space Telescope (HST ), and the Far Ultraviolet Spectroscopic Explorer (FUSE; Long et al 1993Long et al , 1994aLong et al , 2003Sion et al 1994Sion et al , 1995Sion et al , 2003Froning et al 2001;Godon et al 2004). In these data, the WDs are recognizable not only from the broad Ly and Ly absorption lines and the overall shape and flux of the UV spectrum but also from the relatively narrow metal absorption lines, which result from the salting of the atmosphere of the WD by accreting near-solar abundance material.…”
Section: Introductionmentioning
confidence: 67%
“…The GW Lib outburst is reminiscent of the outbursts in the well‐studied system WZ Sge. Studies of the most recent outburst in this system (Kuulkers et al 2002; Patterson et al 2002; Long et al 2003) showed significant heating followed by a long‐term cooling over a number of years (Sion et al 2003; Godon et al 2004, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Another effect to consider is the degree to which short term variations in the accretion history of the CVs being compared compromise the interpretation of T wd as indicative of the long-term (10 5 yr) accretion rates that control the evolutionary history of CVs. Observations of some dwarf novae, e.g VW Hyi (Gänsicke & Beuermann 1996) indicate that a WD returns to a quiescent state within 20 days of outburst, while the WD in WZ Sge had not fully cooled to its pre-outburst temperature 18 months after outburst (Long et al 2003;Sion et al 2003a). These differences likely reflect the different amounts of mass accreted during an outburst, much more in WZ Sge than in VW Hyi.…”
Section: Wd Temperatures In the Context Of CV Evolutionmentioning
confidence: 99%